ANALISIS PERAN ORGANIZATION FOR SECURITY AND CO-OPERATION IN EUROPE (OSCE) DALAM MEDIASI KONFLIK NAGORNO-KARABAKH ANTARA ARMENIA DAN AZERBAIJAN - Jodi Misyendi; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This thesis discusses the role of the Organization for Security and Co-operation in Europe (OSCE) in mediating the Nagorno-Karabakh conflict between Armenia and Azerbaijan.  The Nagorno-Karabakh conflict is a territorial conflict involving Azerbaijan which adheres to the principle of territorial integrity in Nagorno-Karabakh and Armenia which supports the independence of Nagorno-Karabakh and ethnic Armenians over Azerbaijan.  The purpose of writing this thesis is to find out the role of the OSCE in the Nagorno-Karabakh conflict and the factors that influence the failure of OSCE mediation in the resolution of the Nagorno-Karabakh conflict between Armenia and Azerbaijan. This research uses qualitative research methods and library research data collection techniques.  In the discussion, this study uses Jacob Bercovitch's theory of influencing mediation behavior in international conflict as an analytical tool.  The results of this study indicate that OSCE mediation through its representative OSCE Minsk Group, has failed in resolving the Nagorno-Karabakh conflict between Armenia and Azerbaijan.  The failure of OSCE mediation in conflict resolution is influenced by factors of relative power, previous relations, internal characteristics, duration, intensity, issues, previous relationship with parties, previous mediation attempts and mediator strategies.  Meanwhile, the mediator's identity and rank factors have no effect on the failure of the Nagorno-Karabakh conflict mediation. Keywords: Organization for Security and Co-operation in Europe (OSCE), OSCE Minsk Group, Failure, Conflict Mediation, Nagorno-Karabakh, Armenia and Azerbaijan.